2008
DOI: 10.1128/jb.01151-07
|View full text |Cite
|
Sign up to set email alerts
|

LmrR Is a Transcriptional Repressor of Expression of the Multidrug ABC Transporter LmrCD in Lactococcus lactis

Abstract: LmrCD is an ABC-type multidrug transporter in Lactococcus lactis. LmrR encodes a putative transcriptional regulator. In a ΔlmrR strain, lmrCD is up-regulated. LmrR binds the promoter region of lmrCD and interacts with drugs that cause lmrCD up-regulation. This suggests that LmrR is a drug-dependent transcriptional regulator of lmrCD expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
113
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(117 citation statements)
references
References 31 publications
3
113
1
Order By: Relevance
“…About 100 genes involved in cellular metabolism and morphology were found to be differentially expressed in the transcriptome of the cholate-adapted strain. This is in sharp contrast to what was observed in cholate-adapted wild-type L. lactis cells, which showed a prominent defect in the lmrR gene that encodes a transcriptional repressor of lmrCD expression, which resulted in the constitutive expression of the lmrCD genes (1,32). Interestingly, neither the well-characterized transporters LmrA and LmrP nor any of the other remaining putative MDR transporters were found to be upregulated in the cholateadapted ⌬LmrCD r strain, lending further support to the notion that bile acid extrusion is a key activity of LmrCD.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…About 100 genes involved in cellular metabolism and morphology were found to be differentially expressed in the transcriptome of the cholate-adapted strain. This is in sharp contrast to what was observed in cholate-adapted wild-type L. lactis cells, which showed a prominent defect in the lmrR gene that encodes a transcriptional repressor of lmrCD expression, which resulted in the constitutive expression of the lmrCD genes (1,32). Interestingly, neither the well-characterized transporters LmrA and LmrP nor any of the other remaining putative MDR transporters were found to be upregulated in the cholateadapted ⌬LmrCD r strain, lending further support to the notion that bile acid extrusion is a key activity of LmrCD.…”
Section: Discussioncontrasting
confidence: 50%
“…Furthermore, the apparent lack of major extrusion activity in the ⌬LmrCD r cells suggests that LmrCD is the major contributor in cholate extrusion and lends further support for the notion that the cholate resistance of the ⌬LmrCD r strain is unrelated to a transport phenomenon. The expression of the lmrCD genes in L. lactis is controlled by the transcriptional regulator LmrR (1). Previous studies have demonstrated that binding of drugs like Hoechst 33342 and daunomycin to LmrR relieves the repression of the lmrCD genes, thus leading to the manifestation of the MDR phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to this study, the interaction of LmrR with the Hoechst 33342 drug was shown. LmrR, however, is a repressor belonging to the second subfamily of the PadR-like regulators with a short C-terminal domain (49). In contrast to VanR and LmrR, PadR could not be deactivated by the direct binding of phenolic acid as an effector (25).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the function is known for only a few members of the PadR family, which have been shown to play a major role in the biology of their host bacteria. Among these members, (i) AphA from Vibrio cholerae is a quorum sensingregulated activator that initiates the virulence cascade and is a repressor of penicillin amidase activity (pva gene) (18,19,20,23), (ii) LadR from Listeria monocytogenes negatively regulates the expression of the multidrug efflux pump MdrL (17), (iii) LstR is required for effective thermal resistance (35), and (iv) LmrR from Lactococcus lactis regulates the production of LmrCD, a major multidrug ABC transporter (1,25). Crystal structures of two PadR-like proteins, AphA (11) and Pex (5), revealed a protein structure containing a conserved N-terminal winged helix-turn-helix (WHTH) that acts as the DNA-binding motif (4).…”
mentioning
confidence: 99%